Effect of thiadiazine derivatives on intracellular amastigotes of Leishmania amazonensis - Lianet Monzote Fidalgo; Ana Margarita Montalvo Álvarez; Lisset Fonseca Geigel; Rolando Pérez Pineiro; Margarita Suárez Navarro; Hortensia Rodríguez Cabrera (Memorias do Instituto Oswaldo Cruz, 2004)
Current therapy for leishmaniasis is not satisfactory. We describe the in vitro antiproliferative effects of new thiadiazine derivatives against Leishmania amazonensis. The compounds were found to be active against the amastigote form of the parasite, inhibiting parasite growing, from 10 to 89%, at a concentration of 100 ng/ml. This activity suggests that thiadiazine derivatives could be considered as potential antileishmanial compounds.